Laccase-catalyzed decolorization of the synthetic azo-dye diamond black PV 200 and of some structurally related derivatives - Kandelbauer, A. (2004)
The kinetics of laccase-catalyzed transformation of the azo-dye Diamond Black PV 200 (CI Mordant Black 9) and various related synthesized derivatives were analyzed for dependence on pH and substrate structure. The reaction mixture of Diamond Black PV 200 was analyzed by HPLC/MS_/MS and it was shown that upon laccase oxidation, reactive chinoid fragments of lower molecular weight were formed. These may further oligomerize as indicated by the appearance of a number of compounds with increased molecular weight. The pH optimum for the decolorization was pH 5 for Diamond Black PV 200 which did not change significantly when the substitution pattern of its basic structure was varied. Biodegradability, however, was strongly dependent on the structure of the dyes.